Impact of Social Media on Oral Health: A Narrative Review (Academia Journal of Medicine, 2022)
This narrative review delves into the impact of social  media on oral health, examining its influence on  awareness and education, the associated challenges  and risks, strategies to mitigate negative impacts, and  future opportunities. Understanding the multifaceted  impact of social media on oral health is crucial for  developing effective approaches to leverage its  potential and address its pitfalls.
Keywords: Social media; Oral health; Awareness; Education; Challenges; Opportunities